Second-Wave Boycott of Israeli Products as Political Economic Movements - Hidayaturrahman, Mohammad; Alfiyah, Nur Inna; Sudarman, Sudarman; Sinaga, Astriana Baiti; Ubaid, Ahmad Hasan; Sugiantiningsih, Anak Agung Putu; Elazhari, Elazhari (Universitas of Muhammadiyah Makassar, 2024)
Israel's attack on Palestinian Gaza left thousands of people dead, including both women and children. In addition, many public facilities such as hospitals, mosques, and refugee camps were damaged. Sympathy for Palestinian Gaza residents has emerged in various countries worldwide. One of them is in the form of a boycott of products that are indicated to be related to Israel. The purpose of this research was to investigate the motivations behind the boycott of goods and services related to Israel in response to the war launched by Israel in Gaza, Palestine, on October 7, 2023, by some Muslim countries and other democratic nations across the globe. The study aimed to determine whether the boycott was driven by political or economic interests alone. This research is a descriptive qualitative research and data collection technique that searches for documents published in various online media in Indonesia and various other countries. The data analysis technique uses the content analysis of published news. The findings of the study revealed that the primary objective of the boycott, which was to put an end to the war in Gaza, Palestine, was not achieved, as the war continued despite the boycott efforts. However, the study found that the secondary objective, which was to reduce the income of companies with ties to Israeli companies or entrepreneurs, was successfully accomplished. The decline in revenue of these companies, whose products were boycotted in various Muslim countries, indicated that the economic goal of the boycott was achieved. It is important to note that this research had certain limitations, including the time frame of the study, which was conducted over only three months, from October to December 2023.